Persentuhan Unsur-Unsur Historis, Budaya Lokal, dan Islam dalam Ritual Asyura di Desa Pallantikang Kec. Pattallassang Kab. Gowa - Rahmawati; Nurlidiawati; Susmihara; Nuraeni (Universitas Islam Negeri Alauddin Makassar, 2025)
The main problem discussed is how the harmony between historical elements, local culture, and Islam so that it gives birth to a new culture that reflects the harmony and alignment of the three? Next, it is broken down into sub-problems: 1) What is the background of the Ashura ritual in Pallantikang village? 2) What is the symbolic meaning in the Ashura ritual in Pallantikang village and 3) what is the reality of the harmony of historical elements, local traditions, and Islamic values ​​in the Ashura ritual of the community in Pattallassang village, Pattallassang sub-district, Gowa regency? This type of research is classified as qualitative with the research approach used being a historical, anthropological, sociological, and religious approach. Primary sources were obtained from religious and community leaders. While secondary data were obtained from related reading materials. The data collection methods were observation, interviews, and documentation. The results of the study show that the historical element is inseparable from the issue of a major disaster and epidemic that will hit the community so that there is an initiative to take preventive measures (tolak bala'), so coinciding with the day of ashura the community performs the ritual to ward off bala' until today this history is believed from generation to generation. The red and white porridge served during rituals symbolizes life. The reality of the interaction between these three elements lies in the ingredients used, the stories associated with them, the readings read, and the strong beliefs. Pokok masalah yang dibahas adalah bagaimana keserasian antara unsur-unsur historis, budaya lokal, dan Islam sehingga melahirkan budaya baru mencerminkan keserasian dan keselarasan dari ketiganya? Selanjutnya di breakdown menjadi sub masalah: 1) Bagaimana latar belakang ritual asyura di desa Pallantikang? 2) Bagaimana makna simbolik dalam ritual asyura di desa Pallantikang dan 3) bagaimana bentuk realitas keserasian unsur historis, tradisi lokal, dan nilai Islam dalam ritual asyura masyarakat di desa Pattallassang kecamatan Pattallassang kabupaten Gowa? Jenis penelitian ini tergolong kualitatif dengan pendekatan penelitian yang digunakan adalah pendekatan historis, antropologi, sosiologi, dan agama. Sumber primer diperoleh dari tokoh agama dan tokoh masyarakat. Sedangkan data sekunder didapatkan dari bahan bacaan yang terkait. Metode pengumpulan datanya adalah observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa unsur historisnya adalah tidak terlepas dari adanya isu akan adanya bencana besar dan wabah yang akan melanda masyarakat sehingga ada inisiatif untuk melakukan pencegahan (tolak bala’), maka bertepatan dengan hari asyura masyarakat melakukan ritual tolak bala’ hingga hari ini sejarah tersebut diyakini dari generasi ke generasi. Bubur warna merah putih yang disajikan saat ritual sebagai simbol kehidupan. Realitas persentuhan dari ketiga unsur tersebut terletak bahan yang digunakan, kisah yang dikaitkan, bacaan yang dibaca, serta keyakinan yang kuat.